Intraluminal bypass devices as an alternative to protective ostomy for prevention of colorectal anastomotic leakage: a systematic review of the literature. (25th April 2020) - De Hous, N.; Lefevre, J. H.; D'Urso, A.; Van den Broeck, S.; Komen, N.
Abstract: Aim: Anastomotic leakage (AL) is the most important complication of colorectal surgery, leading to high morbidity and mortality. Protective ostomy, the current standard of care for protecting a colorectal anastomosis, has important drawbacks that require the creation of an alternative strategy. Over the past 30 years, several intraluminal bypass devices, designed to shield the anastomosis from the faecal stream, have been developed. The aim of this literature review was to create an updated overview of the devices available and their effectiveness in preventing AL, and to investigate whether they could serve as an alternative to protective ostomy in the future. Method: A systematic review of the literature on intraluminal bypass devices used for preventing colorectal AL was performed. The MEDLINE and Cochrane Library databases were searched, and articles were marked as relevant if an intraluminal bypass device was studied in an animal or human population. Results: The database search yielded 24 relevant articles related to 10 intraluminal bypass devices protecting a colorectal anastomosis. These articles included experimental animal studies, preclinical (pilot) studies, as well as retrospective and prospective clinical studies. Each device was assessed with regard to surgical technique, effectiveness and device‐related complications. Conclusion: Intraluminal bypass devices show promise in preventing AL and its clinical consequences. However, there is insufficient high‐level evidence to draw firm conclusions. There is a need for randomized controlled trials that directly compare these devices with the protective ostomy.